Highly durable all-fiber nanogenerator for mechanical energy harvesting - Zeng, Wei; Tao, Xiao-Ming; Chen, Song; Shang, Songmin; Chan, Helen Lai Wah; Choy, Siu Hong (Energy & environmental science, 2013)
Future generations of wearable electronic systems and mobile communication place a great demand for harvesting energy from ambient environments or human movements. Soft fiber-based electric power generators are attractive in meeting the requirements of wearable devices because of efficient energy conversion performance, high durability and comfort. In this paper, we present a novel all-fiber wearable electric power nanogenerator, which consists of a PVDF-NaNbO sub(3) nanofiber nonwoven fabric as an active piezoelectric component, and an elastic conducting knitted fabric, made from segmented polyurethane and silver coated polyamide multifilament yarns, as the top and bottom electrodes. The non-uniform deformation distribution in a compressed nanogenerator device determines the complex operating modes in the piezoelectric nanofiber nonwoven fabric. The nanogenerator consistently produces a peak open-circuit voltage of 3.4 V and a peak current of 4.4 mu A in cyclic compression tests at 1 Hz and a maximum pressure of 0.2 MPa, which is comparable to normal human walking motion. More importantly, the all-fiber nanogenerator retains its performance after 1 000 000 compression cycles, demonstrating great promise as a wearable energy harvester that converts the mechanical energy of human movement into electricity.